Determinants of Carbon Inventory and Systematic Innovation Methods to Analyze the Strategies of Carbon Reduction: An Empirical Study of Green Lean Management in Electroplating an Factory - Chen, Wei-Hung; Yang, Yen-Ming; Chen, Hsin-Na (Sustainability, 2024)
This study explored the relationship between lean management, carbon inventory, and carbon reduction, along with the main factors affecting factory carbon inventory and carbon reduction, and proposed a set of carbon emission reduction strategies based on green value stream mapping. An electroplating factory and its production line in Taiwan was selected. Fourteen carbon inventory records, three work circle meetings, and green value flowcharts were utilized to collect and analyze data. Furthermore, this study applied the DMAIC framework and TRIZ to solve the issue of carbon emissions. The key factor affecting factory carbon inventory and carbon reduction was found to be electricity waste, which could be reduced through energy-saving methods. After analyzing the green value stream mapping, effective carbon emission reduction can be implemented in the manufacturing process. The company was found to gradually progress towards carbon reduction after investigating seven major green wastes. This study confirms that lean management can help organizations achieve their carbon emission reduction goals and is valuable in improving the organization’s environmental performance and competitiveness.